Assessment of "general movements" in high-risk infants by Prechtl analysis during early intervention period in the first year of life - Mutlu, Akmer; Livanelioğlu, Ayşe; Korkmaz, Ayşe (The Turkish Journal of Pediatrics, 2010)
This study was performed to assess the neurological status of high-risk infants by "general movements" (GMs) method and to compare it with the findings of standard clinical neurological examination and neuroimaging findings during the early rehabilitation period. Neurodevelopmental examination was performed by a neonatologist at the corrected ages of 40 weeks, and 3, 6 and 12 months. Assessment of the physiotherapist included video recording of "Prechtl Analysis of GMs" from the first week of life to the corrected age of 5 months. All infants underwent an early physiotherapy program, and follow-up examinations continued until 12 months. A percentage of agreement of 0.86 was found between cranial ultrasound imaging results and GMs and of 0.78 between neurological examination and GMs. Prechtl analysis was found to be important for detecting neurological dysfunction and differentiating normal neurological development in high-risk infants during the early intervention period. This analysis can be used complementary to other diagnostic and imaging techniques in the follow-up of preterm infants.